Building envelope optimization using geopolymer bricks to improve the energy efficiency of residential buildings in hot arid regions. (December 2022) - Tarek, Dalia; Ahmed, M.M.; Hussein, Hesham Sameh; Zeyad, Abdullah M.; Al-Enizi, Abdullah M.; Yousef, Ayman; Ragab, Ayman
Abstract: This study explored the potential of producing geopolymer bricks from industrial waste including ferrosilicon and aluminum slag. The bricks' physico-mechanical properties show that they conform to many codes and standards. Also, the thermal conductivity of 0.28 W/mK is achieved, which is significantly lower than that of conventional bricks. social residential buildings in New Aswan City, Egypt, is employed as a case study for examining the fabricated bricks' implementation. Using the Design Builder software, it was found that the proposed fabricated brick samples showed energy savings of 5.70–14.90% and a decrease in carbon dioxide emissions of 0.47–7.67% compared to conventional wall brick. The temperature profile reveals that the fabricated brick samples have achieved the desired level of human comfort. Finally, the financial viability of each brick type was analyzed using the simple payback time (SPP). A return on investment of 8.76–15.79 years was determined for the produced brick samples. Therefore, geopolymer bricks are widely recognized as a significant improvement in environmental sustainability. Highlights: Production of geopolymer thermal insulation bricks from alkali-activated industrial waste powder. Using powder of ferrosilicon alloy waste to produce heat-insulating geopolymer bricks (lightweight bricks). The use of aluminum waste as an additive to compensate the lack of alumina in ferrosilicon waste. Study of the effect of binary mixtures of geopolymer bricks on the properties of thermal insulation bricks. Used thermal insulation geopolymer bricks to improve the energy efficiency of residential buildings in hot desert regions.